2022
DOI: 10.1177/15589447221109967
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Distal Forearm Fracture: A Population-Based Study of 5426 Fractures

Abstract: Background: Despite intensive research into the epidemiology of adult distal forearm fractures, the literature is limited. This study aimed to provide a full overview of adult distal forearm fracture epidemiology, including incidence, fracture classification, mode of injury, and trauma mechanism in patients sustaining a distal forearm fracture, based on an accurate at-risk population with manually validated data leading to a high quality in data. Methods: This was a population-based cohort study with a manual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Danish studies showed a decline in incidence rates of forearm fractures between 1995 and 2010 [12]. However, the Danish and Finnish studies showed no change in nationwide incidence rates of distal forearm fractures between 2013 and 2019 [27,28]. Swedish studies showed an increase of the incidence rate of distal forearm fractures between 1999 and 2010 and a decrease between 2001 and 2016 [2,11,14,15].…”
Section: Comparison To Other Studiesmentioning
confidence: 95%
“…Danish studies showed a decline in incidence rates of forearm fractures between 1995 and 2010 [12]. However, the Danish and Finnish studies showed no change in nationwide incidence rates of distal forearm fractures between 2013 and 2019 [27,28]. Swedish studies showed an increase of the incidence rate of distal forearm fractures between 1999 and 2010 and a decrease between 2001 and 2016 [2,11,14,15].…”
Section: Comparison To Other Studiesmentioning
confidence: 95%
“…Distal radius fractures (DRFs) are among the most common bone fractures, with an increasing incidence. [1][2][3][4][5][6] DRFs have a bimodal distribution and peak incidence in young men with high-energy trauma and in women ≥60 years with low-energy trauma due to decreased bone density. 1 National clinical guidelines from the Danish Health Authority recommend 5 weeks of conservative treatment for stable, non-displaced DRFs.…”
Section: Introductionmentioning
confidence: 99%
“…Distal radius fractures (DRFs) are among the most common bone fractures, with an increasing incidence 1–6 . DRFs have a bimodal distribution and peak incidence in young men with high‐energy trauma and in women ≥60 years with low‐energy trauma due to decreased bone density 1 …”
Section: Introductionmentioning
confidence: 99%